THE INFLUENCE OF SPIRITUAL WELL-BEING ON SOCIAL INTERACTION AND ATTITUDES OF TASAMMUH STUDENTS IN ISLAMIC BOARDING SCHOOLS - Firmansyah, Choiron; Ubaidillah, Ubaidillah; Busriyanti, Busriyanti (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Islamic boarding schools engaged in education have long been involved in community-based development as an essential part of forming a tasammuh attitude. This article aims to analyze and measure the intervening role of social interaction on the influence of spiritual well-being on the tasammuh attitude of students at the Miftahul Midad Islamic Boarding School, Lumajang Regency, East Java. This research involved 150 santri parents through an online survey which consisted of social interaction index, the influence of spiritual well-being, and tayammum attitudes. The study results show that 1) The more substantial the spiritual well-being of a santri, the better the pattern of social interaction influences by 77.3%. 2) The better the spiritual well-being of a santri, the better the tasammuh attitude of a santri is to be willing to accept other people's opinions even though they have different religious understandings with an influence of 48.0%. 3) the better the pattern of social interaction, the better the tayammum attitude of a santri to accept other people's opinions even though they have different religious understandings, with an influence of 40.6%. 4) the better the spiritual well-being of a santri, the better it is in social interaction to accommodate an open attitude with others so that santri can have a tayammum attitude to be willing to accept the opinions of others even though they have different religious views.